The Secondary Metabolites Composition of Extracts Genista Quadriflora of Morocco - Lrhorfi, L.Aicha; Dahmani, Fatima Zahra; Elyahyoui, Ouafaa; Berrani, Assia; Samama, Amal; Kerrouri, Saloua; Bengueddour, Rachid (European Scientific Journal, ESJ, 2016)
The strategy adopted by our research team aims at the valorisation of some plants for their importance in the economy Moroccan and their uncertain use. Genista quadriflora (G.Q.), one of those plants that has not been investigated before, is a species of the Fabaceae family of widely used in traditional medicine for its therapeutic properties essentially attributable to natural bioactive compounds. In the present work, in order to optimize the future use of G.Q., extracts were prepared from this plant: one aqueous and the other using organic solvents of increasing polarity: petroleum ether, chloroform, ethyl acetate, and methanol. The yields of dry raw organic extracts are of the order of 0.12%, 2.15%, 7.52 and 18.41 respectively. Preliminary tests and chromatographic analysis (TLC) identify different bioactive molecules. The quantitative determination of total phenols, condensed tannins and flavonoids by the colorimetric method showed that the extracts are rich in these compounds.